2017
DOI: 10.1007/s41101-017-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of Methylene Blue Using Mn3O4 Nanoparticles

Abstract: Mn 3 O 4 nanoparticles were synthesized from one-step reduction of KMnO 4 with glycerol at 80°C. The structural and surface morphological characterizations were carried out using FT-IR, XRD, and FESEM analyses. The elemental composition was evidenced from EDX analysis. XRD analysis showed the tetragonal crystal geometry of Mn 3 O 4 nanoparticles with an average crystallite size of ∼20 nm. The surface morphology of the Mn 3 O 4 nanoparticles was found to be spherical from the FESEM image. The Mn 3 O 4 nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…The elemental composition of the prepared α-MnO 2 nanoparticles was analyzed using EDX analysis as shown in figure 3(a). The lines observed at 5.90, 6.52, 0.64, and 0.52 keV are associated for K (α, β), L lines of the Mn element, and K line of the O elements, respectively [6]. The atomic percentage of Mn and O were 29 and 41 respectively indicating the formation of non-stoichiometric MnO 2 with oxygen vacancy which indicates that the material might show better photocatalytic activity [31].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The elemental composition of the prepared α-MnO 2 nanoparticles was analyzed using EDX analysis as shown in figure 3(a). The lines observed at 5.90, 6.52, 0.64, and 0.52 keV are associated for K (α, β), L lines of the Mn element, and K line of the O elements, respectively [6]. The atomic percentage of Mn and O were 29 and 41 respectively indicating the formation of non-stoichiometric MnO 2 with oxygen vacancy which indicates that the material might show better photocatalytic activity [31].…”
Section: Resultsmentioning
confidence: 93%
“…Nano-manganese oxides have been the focus of various researchers because of their prospective properties and enormous applications in high -Tc semiconductors, high density magnetic storage, electrochemical storage material, solar energy transformation, giant magnetoresistance, ion-exchange material, catalysis, and molecular adsorption [1][2][3][4][5][6]. These wide range of applications and distinctive properties have attracted broad attention to the polymorphic forms of MnO 2 (α-, β-, and γtype).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of several different characterization techniques revealed that addition of manganese ions resulted in Mn 3 O 4 grafted on the surface of the ZnO nanoparticles. Mn 3 O 4 has photocatalytic properties [55,56] but only at a pH below 4 [57]. In the present study, Rhodamine-B, an acidic dye, was used as a model organic pollutant to examine the photocatalytic activity of manganese-added ZnO.…”
Section: Cause Of Conflicting Results In the Past Studiesmentioning
confidence: 99%
“…In our study, the Rhodamine-B solution was highly diluted (0.0096 g/L) to minimize its visible-light absorption and thus had a pH of 6.5. At this near-neutral pH, one cannot expect photocatalytic activity from Mn 3 O 4 alone [57].…”
Section: Cause Of Conflicting Results In the Past Studiesmentioning
confidence: 99%
“…Ullah et al used Mn 3 O 4 nanoparticles for oxidative degradation of methylene blue. [ 9 ] Sreekala et al found that Mn 3 O 4 was an efficient photocatalyst for the removal of Malachite green. [ 10 ] Noble metal nanoparticles have shown remarkable potential for many applications in electronic, chemical, biological, and catalytic fields due to their distinctive properties, when compared to their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%